Synthesis of aziridinosteroids - Di Chenna, P. (2000)
11α,12α-aziridinosteroids (2a, b, c) were prepared from 5β-H-11-pregnene-3, 20-dione (1) using different iminophenyliodinanes and cloramine aziridination reagents.